1983
DOI: 10.3109/10799898309041925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional β-Adrenoceptor Heterogeneity in Central and Peripheral Airway Smooth Muscle of Guinea Pig and Man

Abstract: The nature of the beta-adrenoceptor population(s) mediating the relaxation of guinea pig and human airway smooth muscle was investigated. On the basis of a preferential blockade by beta 1- and beta 2-selective antagonists of the relaxation induced by beta 1- and beta 2-selective agonists, guinea pig tracheal strip relaxation was found to be mediated both by beta 1- and beta 2-adrenoceptors, the relative participation of which depending on the relative affinities of the agonist towards these two receptors. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(11 citation statements)
references
References 13 publications
3
7
0
1
Order By: Relevance
“…The relaxant activity of noradrenaline in human bronchi that we observed was comparable to that observed by Zaagsma et al (1983) who, working on human bronchi obtained post mortem, reported a -log EC,, of 4.60 for noradrenaline, or to the findings of Goldie et al (1984) in human tissue also obtained by autopsy; these authors reported EC,, of 2.02 z t 0.27 and 2.81 k 0.82 pM, respectively, of noradrenaline in preparations under resting tone or precontracted with carbachol to 50% of maximal tension.…”
Section: Discussionsupporting
confidence: 91%
“…The relaxant activity of noradrenaline in human bronchi that we observed was comparable to that observed by Zaagsma et al (1983) who, working on human bronchi obtained post mortem, reported a -log EC,, of 4.60 for noradrenaline, or to the findings of Goldie et al (1984) in human tissue also obtained by autopsy; these authors reported EC,, of 2.02 z t 0.27 and 2.81 k 0.82 pM, respectively, of noradrenaline in preparations under resting tone or precontracted with carbachol to 50% of maximal tension.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our previous findings in PCLS (3), RGZ was able to maintain potency and elicit marked relaxation in maximally contracted trachea, overcoming the functional antagonism shown to limit ␤-adrenoceptor responsiveness (19). Dilator responses mediated through ␤ 2 -adrenoceptors in guinea pig trachea may be of greater relevance to human airways (23,36). The higher potency and efficacy of SALB in tracheal segments from guinea pigs relative to mice are consistent with this, while the finding of marked relaxation to RGZ at similar potency in both species is suggestive of potential benefit independent of ␤-adrenoceptor density.…”
Section: Discussionsupporting
confidence: 77%
“…However, P3-adrenoceptorstimulation has been reported to relax spontaneous tone in the guinea-pig trachea (Zaagsma et al, 1983;Lemoine et al, 1989b). In the present study, T-0509, in contrast to the cardiac muscle, exhibited a relaxant action with a potency 38 times less than isoprenaline through 132-adrenoceptors in the histamine-contracted trachea, but with a similar intrinsic activity to isoprenaline.…”
Section: Discussionmentioning
confidence: 50%